2016
DOI: 10.1101/gad.288035.116
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of intestinal stem cells by Tet1-mediated DNA hydroxymethylation

Abstract: Methylated cytosines are associated with gene silencing. The ten-eleven translocation (TET) hydroxylases, which oxidize methylated cytosines to 5-hydroxymethylcytosine (5hmC), are essential for cytosine demethylation. Gene silencing and activation are critical for intestinal stem cell (ISC) maintenance and differentiation, but the potential role of TET hydroxylases in these processes has not yet been examined. Here, we generated genome-wide maps of the 5hmC mark in ISCs and their differentiated progeny. Genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 39 publications
(49 reference statements)
5
42
3
Order By: Relevance
“…In addition, stable accumulation of 5hmC has been described for enterocyte differentiation in well-known TF binding sites and targets involved in this process [75,76]. This contrasts with the pattern shown for blood cell subtypes, at least at earlier stages of blood cell differentiation (i.e., from HSCs) [19], in which there is a more general presence of 5hmC followed by a global drop that respects lineage-related loci, as described above.…”
Section: Endodermcontrasting
confidence: 40%
“…In addition, stable accumulation of 5hmC has been described for enterocyte differentiation in well-known TF binding sites and targets involved in this process [75,76]. This contrasts with the pattern shown for blood cell subtypes, at least at earlier stages of blood cell differentiation (i.e., from HSCs) [19], in which there is a more general presence of 5hmC followed by a global drop that respects lineage-related loci, as described above.…”
Section: Endodermcontrasting
confidence: 40%
“…We therefore analysed distribution of 5mC and 5-hydroxymethylcytosine (5hmC) (37) at H3K27Ac positive distal elements in intestinal epithelial cells. Here, we considered that at least one MBD/ MeDIP peak (150 bp) must overlap with H3K27Ac positive region.…”
Section: Resultsmentioning
confidence: 99%
“…These mice are smaller than their litermate controls and ultimately deletion of Tet1 is lethal. Furthermore, LGR5 + cells derived from these TET1-deicient mice are also unable to form organoids, which conirms the role of TET1 and hydroxymethylation as a critical step in epithelial cell diferentiation and maintenance [33,35].…”
Section: Intestinal Epithelial Cellsmentioning
confidence: 65%
“…These studies showed relatively similar levels of methylation in the crypts and in association with rapidly dividing (Ki67+) cells in the transition zone; whereas, there was an enrichment of hydroxymethylation at the tips of the villi and a decreased prevalence of hydroxymethylation in the crypts in Ki67-positive cells. These data suggest that hydroxymethylation is gained during diferentiation and preferentially expressed in non-dividing, terminally diferentiated cells [33].…”
Section: Intestinal Epithelial Cellsmentioning
confidence: 82%
See 1 more Smart Citation